DEVELOPING SECURED INTEROPERABLE CLOUD COMPUTING SERVICES - Z., Al-Khanjari; A., Alani (European Scientific Journal, ESJ, 2014)
Developers of cloud computing systems are responsible for identifying the requirements of Quality Attributes and developing security of cloud computing systems. Developing a quality cloud computing systems needs to satisfy interoperability, security, safety, dependability, performance, and other. Security of cloud computing services represents another incentive that will promote the use of cloud services by related stakeholders. Also, security is considered as an important issue when dealing with cloud services’ interoperability. Using good protected access control technique can prevent many security problems. This paper proposes steganography scheme as a new architecture to secure the data in cloud computing by exploiting text properties. Also, it describes the implementation of the data steganography technique, which could provide more security to the cloud computing environment to achieve the trusted computing technology.